Taxonomic review of Eidmanacris Chopard, 1956 (Orthoptera: Grylloidea: Phalangopsidae) - Campos, Lucas Denadai De; Souza-Dias, Pedro G. B.; Nihei, Silvio S. (Zootaxa, 2017)
Eidmanacris Chopard, 1956 is revised, redescribed and eleven species are redescribed. Seven new species from the Brazilian Atlantic Forest and Cerrado (E. scopula Campos sp. nov., E. gigas Campos sp. nov., E. neomarmorata Campos, sp. nov.; E, desutterae Campos, sp. nov.; E. putuhra Campos, sp. nov.; E. fontanettiae Campos, Nihei & de Mello, sp. nov. and E. melloi Campos, sp. nov.) are described, based on adults. One new generic synonymy with Endophallusia de Mello, 1990 syn. nov., resulting in two new combinations (E. minuta (de Mello, 1990) comb. nov. and E. endophallica (de Mello, 1990) comb. nov.), a new combination with Phalangopsis spelucae Mello-Leitão, 1937 (E. speluncae (Mello-Leitão, 1937) comb. nov.), and one species synonymy (E. lencionii Bolfarini, 2016 = E. dissimilis Desutter-Grandcolas, 1995, syn. nov.) are proposed. Following this revision, Eidmanacris comprises a total of 29 species. An identification key to species, and distribution maps are also given.